Etika Komunikasi Islam dalam Praktik Kepemimpinan Kolaboratif Bobby Nasution di Sumatera Utara - Dalimunthe, Ahmad Ridwan; Rubino, Rubino; Ritonga, Hasnun Jauhari (Lembaga Teewan Journal Solutions, 2026)
Leadership communication is shaped not only by message delivery but also by the ethical values underlying relationships between leaders, communities, and stakeholders. This study analyzes the implementation of Islamic communication ethics in Bobby Nasution's collaborative leadership in North Sumatra, using a qualitative case study design. Informants were purposively selected from government officials, academics, socio-political observers, community leaders, and youth representatives. Data were collected through in-depth interviews, observation, and documentation, then analyzed via reduction, display, and conclusion verification, with triangulation strengthening credibility. Three findings emerged. First, leadership communication was marked by simple, clear, and solution-oriented language, supported by nonverbal cues and direct community engagement; public trust depended on consistency between messages, actions, and equitable development outcomes. Second, collaborative leadership was practiced through intergovernmental coordination, deliberation, public consultation, field visits, and involvement of religious leaders, academics, media, and the private sector, though follow-up mechanisms for public aspirations need strengthening. Third, the values of shiddiq, trustworthiness, syura, qaulan sadīdan, balīghan, layyinan, and ma'rūfan were reflected in truthful information, respectful language, and policy accountability. The study concludes that Islamic communication ethics require alignment among messages, deliberation, action, and public welfare.